PENGARUH PARKIR DI BADAN JALAN TERHADAP KINERJA RUAS JALAN CAK DOKO - Engelbertha N.B. Seran; Maria Junita Klau (Eternitas: Jurnal Teknik Sipil, 2022)
Management of on-street and off-street parking is important in controlling traffic so that congestion, pollution, noise can be reduced, and in turn it can improve environmental quality standards, the quality of pedestrians and cyclists movement (Hobbs, 1995) . One of the cases that hinders traffic flow and reduces the level of road service on Jalan Cak Doko is the presence of many public facilities such as offices, restaurants and shops in the area. This study aims to examine road performance on the Cak Doko street section. Analysis using the Indonesian Road Capacity Manual method shows that the performance of the road segment is poor, with a degree of saturation for the existing condition of 0.77 and for the no-parking condition of 0.72. The LoS value for existing conditions reaches 0.77 (Category E) where the traffic volume approaches or is at an unstable flow capacity and sometimes stops. And LoS for no parking conditions is 0.72 (Category D) where the flow is approaching unstable, the speed is still controlled and the Q/C level is still acceptable. The dominant cases that contribute to traffic congestion and reduce the level of road service are on-street parking activities. In order to improve road performance, one aspect of improvement is the management of on-street parking activities.